2021
DOI: 10.3390/en14061539
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Alternative Sources of Thermal Energy in the Production of Cement—An Impact on CO2 Emission

Abstract: The article evaluates the reduction of carbon dioxide emission due to the partial substitution of coal with alternative fuels in clinker manufacture. For this purpose, the calculations were performed for seventy waste-derived samples of alternative fuels with variable calorific value and variable share in the fuel mixture. Based on annual clinker production data of the Polish Cement Association and the laboratory analysis of fuels, it was estimated that the direct net CO2 emissions from fossil fuel combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…The CO2-eq emission from a cement manufacturing plant is originated from the decarbonization of the raw materials (CaCO3 → CaO +CO2) and combustion of carbon (C + O2 → CO2) in the fuels used for providing energy for the overall endothermic reactions in the kiln system (Lin, Kiga, Wang, & Nakayama, 2011;Wojtacha-Rychter, Kucharski, & Smolinski, 2021). Hence, the emissions generated from the combustion of IWSF in a cement manufacturing plant were predicted via the stoichiometric method.…”
Section: G Co2-eq Emission From the Use Of Iwsfmentioning
confidence: 99%
“…The CO2-eq emission from a cement manufacturing plant is originated from the decarbonization of the raw materials (CaCO3 → CaO +CO2) and combustion of carbon (C + O2 → CO2) in the fuels used for providing energy for the overall endothermic reactions in the kiln system (Lin, Kiga, Wang, & Nakayama, 2011;Wojtacha-Rychter, Kucharski, & Smolinski, 2021). Hence, the emissions generated from the combustion of IWSF in a cement manufacturing plant were predicted via the stoichiometric method.…”
Section: G Co2-eq Emission From the Use Of Iwsfmentioning
confidence: 99%
“…The elemental analysis of the RDF samples from several municipal solid waste management plants [41] and a cement plant in Poland [42] showed that the carbon content ranged from 30 to 60% for waste fuels. In comparison, the carbon content in fossil fuels increased to over 90% (for anthracite [43]). Bielowicz et al [44,45] presented the chemical analysis of the share of elements in 28 coal samples including low-rank and bituminous coal samples derived from the Coal Basin in Poland and showed that the carbon content ranged from 63.40% (lignite) to 89.73% (coking coal).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the environmental and economic advantages in terms of the use of RDF and sewage sludge in cement plants was the objective of this paper. The benefits of a cement plant working on coal and partly replacing fossil fuels with an alternative fuel have been presented in many works [43,46,47]. The authors of [43] provided a benefits-based case study where the substitution of 10-90% coal with the alternative fuel was assumed.…”
Section: Introductionmentioning
confidence: 99%
“…This includes, for example, plants intended to treat food-industry waste [8][9][10][11] and hospital waste [12][13][14]. In some studies, models of the interdependence between combustion-process emission parameters and other important factors, such as 2 of 11 waste-to-energy, were highlighted and presented [15][16][17][18][19][20]. Examples of methods for reducing the emission of harmful compounds are included in the articles [21][22][23].…”
Section: Introductionmentioning
confidence: 99%